The Distant Roar of Battle: The Italian Film Criticism Unions in the Press of the Period - Matteo Berardini (Cinergie, 2023)
Throughout the twentieth century, Italian film criticism ran into various moments of crisis; three of these triggered the foundation of a union organization, a political instrument with little affinity for the intellectual elites and yet cyclically present in the history of our criticism. The years in question are 1916, 1925 and 1971, to which we owe, respectively, the Syndicate of the Film Press, the Syndicate of Intellectuals of Cinematography and the National Syndicate of Italian Film Critics. They are profoundly different moments and in any case in dialogue with each other, as phases of an identity repositioning in which the professional and ideological, political and social levels intersect. The aim of this essay is therefore to recover the studies that interpret the discursive practice of criticism as an entity ontologically connected to a state of crisis (de Man, Frey) to place them in a more accentuated historical framework. To do so, the three quoted periods will be reconstructed and analysed, using an archival corpus of period press as sources, and the cultural industry as an additional theoretical framework in the context of Italian literary theory of the sixties (Ferretti, Fortini), in order to restore facets and complexities of crisis that would otherwise not be resolved in purely endemic and ontological terms.